Effect of Encapsulation into Alginate Microspheres on Viability of Mesenchymal Stromal Cells after Exposure with Penetrating Cryoprotectants - Zaikov, Vedeney S.; Tarusin, Dmitriy N.; Petrenko, Aleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2016)
The effect of encapsulation into alginate microspheres (AMS) on viability of mesenchymal stromal cells (MSCs) after exposure to the solutions of penetrating cryoprotectants dimethyl sulfoxide (DMSO), ethylene glycol (EG) and 1,2-propane diol (1,2‑PD) with concentrations varying from 1.5 to 9 M during 1.5 and 5 min was studied. It was shown that the viability of MSCs both as a suspension and encapsulated in AMS decreased with a rise in cryoprotectant concentration and exposure time. Encapsulation into AMS significantly protected the cells from cytotoxic damage of the cryoprotectants, e. g. if the 5-min exposure to 9 M DMSO, EG and 1,2-PD resulted in the death of quite all the cells in the suspension, the viability of encapsulated MSCs after exposure under similar conditions made 60, 80 and 52% respectively. It was found that the studied penetrating cryoprotectants had a various cytotoxicity to MSCs, and it decreased in the row DMSO > 1,2-PD > EG. The findings can be used to develop a multi-component vitrifying solution. Probl Cryobiol Cryomed 2016; 26(3): 213–220